The Syntax Features of the African American English In Georgia Doyle Johnson's Frederick Douglas And Loraine Hansberry's A Raisin in the Sun - Sadiq, Nizamuddin (English Education Department, Universitas Islam Indonesia, 2008)
Syntax reflects features of a language. One of the American African English features in syntax can be seen in Georgia Doyle Johnson's Frederick Douglas and Loraine Hansberry's A Raisin in the Sun. As it is considered non-standard dialect, the American African English syntax is assumed to have its own characteristic different from the standard American English. This paper is descriptive linguistics rather than a stylistic study as it does not focus on literary style. The data taken was classified into linguistic elements and was